THE RELATIONSHIP BETWEEN DENTAL HEALTH PERCEPTION AND DENTAL SERVICE UTILIZATION AMONG SCHOOL CHILDREN IN SOUTH JAKARTA - Januar, Paulus (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2020)
Background: the utilization of dental service is an important factor inoral health. The utilization of dental service is affected by the perception and the importance that the person gives to their oral health and needs. The objective of the study was to analyze the relationship between the perception of dental health and utilization of dental service. Method: a qualitative analytical cross-sectional study was conducted among 120 students of 12 elementary schools in south Jakarta, selected using a proportional sampling method. A questionnaire was administered to elicit data on dental health perception and dental service utilization. Result: Most students perceived their dental health as good and never had dental sickness. Almost half of the sample never utilized dental service and the utilization of dental service mostly for extracting and filling the teeth. Chi-square test showed significant difference between the perception of the occurrence of dental sickness with the frequency and pattern of dental service utilization and no significant difference between the perception of the health of teeth and oral soft tissue with the utilization of dental service. Conclusions: there were relationships between the perception of the occurrence of dental sickness with the frequency and with the pattern of dental service utilization. There was no relationship between the perception of the healthy teeth and oral soft tissue with the utilization of dental service.